Knowledge, Attitudes, and Practices Toward Healthy Diet Among Reproductive Age Women in a Rural Lahore Community - Rasheed, Tooba; Rubab, Mishal; Ayesha, Hafiza; Baig, Ayesha; Butt, Muhammad Bilal; Haider, Ali; Shahid, Ayesha; Ashraf, Mehak (Biological and Clinical Sciences Research Journal, 2025)
Women of reproductive age are particularly vulnerable to the consequences of poor nutrition, which can adversely impact both maternal and child health. Limited access to nutritional information and resources, especially in rural communities, increases the risk of deficiencies. Understanding knowledge, attitudes, and practices (KAP) regarding healthy diets among this population is essential for designing culturally appropriate interventions. Objective: To assess the knowledge, attitudes, and practices toward a healthy diet among reproductive-age women in a rural community of Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 120 women aged 15–49 years residing in Lakhodair, Lahore. Participants were recruited through convenience sampling. Data were collected using a structured, pre-tested questionnaire adapted from validated sources, covering demographics, knowledge, attitudes, and practices related to diet. Knowledge, attitudes, and practices were categorized as good/positive when more than 50% of responses were affirmative. Data were analyzed using SPSS version 22, with descriptive statistics presented as frequencies and percentages. Ethical approval was obtained from the Institutional Review Board, and informed consent was taken. Results: Among 120 participants, the majority were aged 26–35 years (37.5%), married (75.8%), and housewives (68.3%). Educational status was low, with 18.3% having no formal education and only 15.8% achieving higher education. Most women (74.2%) demonstrated good knowledge of dietary fiber, vitamins, and high-fat foods; however, gaps remained in awareness about folic acid (56.7%) and iron-rich foods (57.5%). Attitudes were predominantly positive, with 88.3% expressing favorable views on healthy eating. Dietary practices were also encouraging, with 90% of respondents reporting good practices, including the consumption of freshly cooked food, family meals, and traditional diets. Conclusion: The study reveals that women in rural Lahore generally possess good knowledge, positive attitudes, and favorable practices regarding healthy diets. However, critical gaps remain in awareness regarding micronutrients such as iron and folic acid. Targeted nutrition education programs addressing these gaps, along with strategies to improve access to quality food, are essential for strengthening maternal and child health outcomes in rural Pakistani settings.